Meningkatkan Keterampilan Praktis Siswa dalam Energi Hijau Melalui Proyek Berbasis Pembelajaran Elektronika Industri - Yunesman Yunesman; Ambiyar Ambiyar; Ismail Panessai (International Journal of Learning and Education, 2025)
This study investigates the effectiveness of project-based learning (PjBL) in enhancing students’ practical skills in green energy within industrial electronics education at a higher education institution in Batam, Indonesia. The pressing global demand for a workforce competent in renewable energy technologies necessitates pedagogical innovations that bridge the gap between theoretical knowledge and industry-required practical competencies. Employing a quasi-experimental mixed-methods design, 63 second-semester students in the Industrial Engineering Department of Ibnu Sina University were divided into experimental (n=31) and control (n=32) groups. The experimental group engaged in PjBL focused on designing a solar panel system with microcontroller integration, while the control group followed conventional instructional methods. Data were collected through pre-tests, post-tests, structured observation rubrics, and reflective journals. Statistical analysis using paired-sample t-tests revealed a significant improvement in practical skills for the experimental group (pre-test M=57.4; post-test M=81.6; p<0.001), substantially exceeding the control group’s improvement (pre-test M=56.9; post-test M=65.3). Qualitative findings corroborated these results, indicating heightened student engagement, collaborative problem-solving, and deeper conceptual understanding of renewable energy systems. The findings contribute to the growing body of literature on PjBL implementation in STEM-based vocational higher education and offer practical implications for curriculum design aligned with green industry workforce demands.